2013
DOI: 10.1016/j.ejphar.2013.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate induced contraction of bladder smooth muscle

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid that contracts most smooth muscles. Although S1P has been shown to contract bladder smooth muscle, the mechanism(s) by which S1P initiates contraction has not been extensively investigated. The goal of this study was to determine if S1P-induced force generation and myosin light chain (MLC) phosphorylation are dependent on calcium sensitization pathways mediated by protein kinase C (PKC) and Rho kinase (ROCK) and which S1P receptor is important in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The S1P 2 receptor induces contraction of diverse types of smooth muscle, including vascular, bronchial, intestinal, and bladder smooth muscle, by inducing increases in intracellular Ca 2+ concentration and activation of Rho/Rho kinase ( Ohmori et al, 2003 ; Hu et al, 2006 ; Kendig et al, 2013 ). In the vascular system, endothelial S1P 1 and S1P 3 receptors mediate NO-dependent vasodilation, while smooth muscle S1P 2 and S1P 3 receptors mediate vasoconstriction, with differential responses in different vascular beds ( Igarashi and Michel, 2009 ; Kerage et al, 2014 ).…”
Section: Contractile Effect Of S1p 2 In Smooth Musmentioning
confidence: 99%
“…The S1P 2 receptor induces contraction of diverse types of smooth muscle, including vascular, bronchial, intestinal, and bladder smooth muscle, by inducing increases in intracellular Ca 2+ concentration and activation of Rho/Rho kinase ( Ohmori et al, 2003 ; Hu et al, 2006 ; Kendig et al, 2013 ). In the vascular system, endothelial S1P 1 and S1P 3 receptors mediate NO-dependent vasodilation, while smooth muscle S1P 2 and S1P 3 receptors mediate vasoconstriction, with differential responses in different vascular beds ( Igarashi and Michel, 2009 ; Kerage et al, 2014 ).…”
Section: Contractile Effect Of S1p 2 In Smooth Musmentioning
confidence: 99%
“…One or more of these receptors have been reported to mediate the contractile effect of S1P in a variety of smooth muscle preparations. It has been reported that S1P-induced contractions were mediated via S1PR2 receptors in the urinary bladder [ 28 , 31 , 37 ], myometrium [ 25 ], airway smooth muscle [ 26 ], esophageal [ 27 ] and gastric smooth muscle [ 29 , 46 ]. S1P-induced contraction of gastric smooth muscle is also mediated in part by S1PR1 receptors [ 29 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Chiba et al (2010), S1P-induced contraction of murine bronchial smooth muscle was abolished by Y-27632, an inhibitor of Rho kinase indicating a role for Rho-kinase pathway of calcium sensitization in S1P-induced contraction of the bronchial smooth muscle. The Rho kinase pathway of calcium sensitization has also been implicated in S1P-induced contraction of guinea-pig trachea [ 38 ], urinary bladder [ 31 , 37 ], human airway smooth muscle [ 26 ] and porcine retinal arterioles [ 51 ]. Kim et al have reported a role for the PKC pathway of calcium sensitization in S1P-induced contraction of feline esophageal smooth muscle cells [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingosine-1-phosphate is a sphingosine signaling molecule involved in lymphoid cell migration, angiogenesis, and smooth muscle contraction. [11][12][13][14] Animal studies have suggested a role in bladder function and dysfunction. Sphingosine-1-phosphate can induce contraction of detrusor muscle strips ex vivo.…”
Section: Why This Mattersmentioning
confidence: 99%